Improved Environmental Genomes via Integration of Metagenomic and Single-Cell Assemblies - Mende, Daniel R.; Aylward, Frank O.; Eppley, John M.; Nielsen, Torben N.; DeLong, Edward F. (Frontiers in Microbiology, 2016)
Assembling complete or near complete genomes from complex microbial communities remains a significant challenge in metagenomic studies. Recent developments in single cell amplified genomes (SAGs) have enabled the sequencing of individual draft genomes representative of uncultivated microbial populations. SAGs suffer from incomplete and uneven coverage due to artifacts that arise from multiple displacement amplification (MDA) techniques. Conversely, metagenomic sequence data does not suffer from the same biases as SAGs, and significant improvements have been realized in the recovery of draft genomes from metagenomes. Nevertheless, the inherent genomic complexity of many microbial communities often obfuscates facile generation of population genome assemblies from metagenomic data. Here we describe a new method for metagenomic-guided SAG assembly that leverages the advantages of both methods and significantly improves the completeness of initial SAGs assemblies. We demonstrate that SAG assemblies of two cosmopolitan marine lineages–Marine Group 1 Thaumarchaeota and SAR324 clade bacterioplankton–were substantially improved using this approach. Moreover, the improved assemblies strengthened biological inferences. For example, the improved SAR324 clade genome assembly revealed the presence of many genes in phenylalanine catabolism and flagellar assembly that were absent in the original SAG.